Tony's bread : an Italian folktale - DePaola, Tomie (New York : G. P. Putnam's Sons, 1989)
A baker loses his daughter but gains a bakery in the grand city of Milano after meeting a determined nobleman and baking a unique loaf of bread.
Keywords: Children's stories